Listening skills through rhymes and minimal pairs with consonant sounds - Chulde Cabrera, Sandra Valentina (2022)
This research presents a proposal based on Listening Skills through Rhymes and Minimal Pairs with Consonant Sounds aimed at students of four to five years old in a kindergarten at “San Francisco de Sales High School” located in Quito, during the 2021-2022 school year. The methodology used in the development of the proposal is of an experimental type, because the General Objective is to develop pre-listening skills through the use of minimal pairs with consonant sounds and rhymes. This tool will show the differences of learning through rhymes, as well as the use of minimal pairs and their identification through IPA symbols and sounds in children. To extract the information, the survey technique was applied to a population of 7 teachers and 7 kindergarten students. The application of the survey presents the knowledge about minimal pairs and phonological awareness that teachers in the institution have, as well as the necessities to focus on certain minimal pairs with consonant sounds that are difficult to distinguish in higher levels. Likewise, it allowed us to see the development of students´ listening skills and pronunciation.